A dimensional classification of autism spectrum disorder by social communication domains - Tanguay, P E; Robertson, J; Derrick, A (Journal of the American Academy of Child and Adolescent Psychiatry, 1998)
To investigate whether "social communication" could be used to assess severity of symptoms in autism spectrum disorder. Social communication refers to the communication of cognitive and emotional information through facial expression, gesture, and prosody and through implicit understanding of pragmatics and of theory of mind. Subjects were evaluated by raters using the Autism Diagnostic interview-Revised and either the Autism Diagnostic Observation Schedule or the Pre-Linguistic Autism Diagnostic Observation Schedule. Two investigators independently diagnosed autism, Asperger's disorder, or pervasive developmental disorder-not otherwise specified in 63 subjects. Items from the Autism Diagnostic Interview-Revised that were judged to represent social communication behaviors were factor-analyzed. Three factors were identified: affective reciprocity, joint attention, and theory of mind. Comparing this new classification approach to DSM-IV led to suggestions for possible changes in the latter: (1) Vocabulary and grammar deficiencies in autistic persons should be coded under developmental language disorder, (2) The diagnosis of Asperger's disorder may not be needed. (3) Requiring that all persons with autism spectrum disorder have a symptom from the "restrictive, repetitive, and stereotypic" list may need to be reconsidered. The DSM-IV category of pervasive developmental disorder may be ideal for diagnosing "classic" autism, but it may be inadequate for diagnosing less severe forms of the disorder.